The distribution of debt across euro area countries: The role of individual characteristics, institutions and credit conditions - Olympia Bover; Jose Maria Casado; Sonia Costa; Philip Du Caju; Yvonne McCarthy; Eva Sierminska; Panagiota Tzamourani; Ernesto Villanueva; Tibor Zavadil (National Bank of Belgium, 2013)
The aim of this paper is twofold. First, we present an up-to-date assessment of the differences across euro area countries in the distributions of various measures of debt conditional on household characteristics. We consider three different outcomes: the probability of holding debt, the amount of debt held and, in the case of secured debt, the interest rate paid on the main mortgage. Second, we examine the role of legal and economic institutions in accounting for these differences. We use data from the first wave of a new survey of household finances, the Household Finance and Consumption Survey, to achieve these aims. We find that the patterns of secured and unsecured debt outcomes vary markedly across countries. Among all the institutions considered, the length of asset repossession periods best accounts for the features of the distribution of secured debt. In countries with longer repossession periods, the fraction of people who borrow is smaller, the youngest group of households borrow lower amounts (conditional on borrowing), and the mortgage interest rates paid by low-income households are higher. Regulatory loan-to-value ratios, the taxation of mortgages and the prevalence of interest-only or fixed-rate mortgages deliver less robust results.
Keywords: D14; G21; G28; K35; 330; Household debt and interest rate distributions; Time to Foreclose; Taxation; Loan-to-Value ratios; Fixed rate mortgages; Financial literacy; Private Verschuldung; Hypothek; Vergleich; Eurozone